Prevalence of Antimicrobial Resistance and Hemolytic Phenotypes in Culturable Arctic Bacteria - Mogrovejo, Diana C.; Perini, Laura; Gostinčar, Cene; Sepčić, Kristina; Turk, Martina; Ambrožič-Avguštin, Jerneja; Brill, Florian H. H.; Gunde-Cimerman, Nina (Frontiers in Microbiology, 2020)
Many Arctic biomes, which are populated with abundant and diverse microbial life, are under threat: climate change and warming temperatures have raised concerns about diversity loss and possible emergence of pathogenic microorganisms. At present, there is little information on the occurrence of Arctic virulence-associated phenotypes. In this study we worked with 118 strains of bacteria (from 10 sampling sites in the Arctic region, located in Greenland and the Svalbard Archipelago) isolated using R2A medium. These strains belong to 4 phyla and represent 36 different bacterial genera. Phenotypic resistance to 8 clinically important antimicrobials (ampicillin, chloramphenicol, ciprofloxacin, cefotaxime, erythromycin, imipenem, kanamycin, and tetracycline) and thermotolerance range were determined. In addition, a screening of all isolates on blood agar media and erythrocytes suspension of bovine and sheep erythrocytes for virulence-linked hemolytic activity was performed. Although antimicrobial resistance profiles varied among the isolates, they were consistent within bacterial families and genera. Interestingly, a high number of isolates (83/104) were resistant to the tested concentration of imipenem (4 mg/L). In addition, one third of the isolates showed hemolytic activity on blood agar, however, in only 5% of the isolates hemolytic activity was also observed in the cell extracts when added to erythrocyte suspensions for 60 min. The observed microbial phenotypes contribute to our understanding of the presence of virulence-associated factors in the Arctic environments, while highlighting the potential risks associated with changes in the polar areas in the light of climate change.